Peran Foto Produk Sebagai Branding UMKM di Kelurahan Gebang Putih - Roziana Febrianita; Fadhiatus Zahro; Melyssa Safira Anwar; Akmal Nugraha Ramadhan (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
Micro, Small, and Medium Enterprises or MSMEs can be said to be the driving force for the national economy and employment. Its contribution to Indonesia's economic growth reached 99% of all business units. The community service team from UPN "Veteran" East Java made observations by going directly to the field, especially in the Gebang Putih area, Surabaya. Behind the success of SMEs there is a problem. Where the majority of MSMEs admit that they do not have attractive product photos. Therefore, the service team has a solution to this problem, namely holding training activities and product photo assistance asbranding MSMEs in Gebang Putih Village. This activity uses various methods, the first is the observation stage, the second is the counseling stage, then the training stage and the last is the mentoring stage. That way, MSME actors will understand more about the importance of product photos asbranding of their business products.